Clinico-radiological and functional outcome of surgical management of displaced two part, three part and four part proximal humeral fractures in adults treated by PHILOS plate in a tertiary care hospital in North India: a prospective study of 30 patients - Spolia, Pankaj; Ghani, Abdul; Arfee, Sakib (International Journal of Research in Medical Sciences, 2021)
Background: Treatment of proximal humeral fractures is challenging. In the past, the fractures were treated conservatively which compromised the functional results. PHILOS plate provides a good functional outcome with context to the early joint mobilization and rigid fixation of the fracture. Methods: This was the prospective study of 30 patients aged 20 to 60 years (mean age 48.4 years) with proximal humeral fractures including two part, three part and four part fractures based on Neer’s classification, treated by open reduction internal fixation with PHILOS plating. Functional outcome was assessed using Constant-Murley Score. Results: The final outcome was observed at 6 months follow up. The results were comparable with the existing literature. The Mean Constant Score at 6 month follow up was 79.4, range (38 to 92). Out of 30, (n = 12, 40%) had excellent outcome, (n = 9, 30%) had good functional outcome, 6 (20%) had moderate outcome, 3 (10 %) had poor outcome. Out of 30 patients, one patient with four part fracture had a lowest CS of 38. Complications were observed in 5, (16.7%) patients. Varus malunion in one patient, avascular necrosis in one patient, stiffness in one patient. Conclusions: PHILOS plate gives stable fixation, enables early range of motion and minimizes complications with good functional outcome if done with expert hands.